Grade 12 rural teachers’ Technological Pedagogical Content Knowledge and challenges while using GeoGebra to teach Euclidean geometry - Malale, Masantsa Tshegofatso; Mbhiza, Hlamulo Wiseman (Frontiers in Education, 2025)
IntroductionThe integration of dynamic mathematics software like GeoGebra in recent years into classroom teaching has gained international attention for its potential to enable learners’ conceptual understanding in geometry. This study explores the challenges teachers face in integrating GeoGebra into Grade 12 Euclidean geometry lessons, addressing significant gaps in the literature regarding technology use in rural educational settings.MethodsQualitative data from semi-structured interviews, classroom observations, and Video-Stimulated Recall Interviews with five teachers reveal that inadequate training in Technological Knowledge (TK) limits teachers’ ability to effectively employ GeoGebra, resulting in issues such as inaccuracies in geometric representations and reduced learner engagement.ResultsObservations indicate variation in classroom environments where infrastructural support directly impacts the effectiveness of technology integration in mathematics teaching. The study further highlights effective pedagogical strategies, as evidenced by teachers’ proactive use of GeoGebra during the observed lessons. Participants express a strong desire for more structured professional development to improve their technology integration skills, emphasizing the critical need for comprehensive training programs.DiscussionUltimately, this research contributes to international literature by highlighting the necessity of robust pedagogical and technological foundations for teachers, thereby advocating for ongoing professional development that equips teachers with the skills required to integrate technology effectively in geometry education.